2010
DOI: 10.1111/j.1365-3024.2009.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Helminth infection inhibits airway allergic reaction and dendritic cells are involved in the modulation process

Abstract: Several previous studies have demonstrated that some helminth infections can inhibit allergic reactions, but the examination on the effect of live Schistosoma japonicum (SJ) infection on allergic inflammation remains limited. The aim of this study was to examine the effect and mechanism of chronic SJ infection on airway allergic inflammation in a murine model. The data showed that chronic SJ infection suppressed airway eosinophilia, mucus production and antigen-specific IgE responses induced by ovalbumin (OVA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 39 publications
3
37
0
1
Order By: Relevance
“…Exposure to other helminths such as S. mansoni (9799), S. japonicum (100) or T. spiralis (101) also affords protection from allergic airway reactivity and inflammation. Helminth exposure is associated with decreased OVA-stimulated IL4 and IL5, but increased IL10 and TGFβ production as measured in either bronchoalveolar lavage fluid or supernatants from cultured pulmonary draining lymph node cells or splenocytes.…”
Section: Helminths and Other Immune Mediated Diseasesmentioning
confidence: 99%
“…Exposure to other helminths such as S. mansoni (9799), S. japonicum (100) or T. spiralis (101) also affords protection from allergic airway reactivity and inflammation. Helminth exposure is associated with decreased OVA-stimulated IL4 and IL5, but increased IL10 and TGFβ production as measured in either bronchoalveolar lavage fluid or supernatants from cultured pulmonary draining lymph node cells or splenocytes.…”
Section: Helminths and Other Immune Mediated Diseasesmentioning
confidence: 99%
“…The role of Tregs in infection-mediated inhibition of allergy has been documented in studies on parasitic infections, especially helminth infections. [58][59][60][61][62][63] The involvement of Tregs in bacterial infectionmediated modulation of allergy/asthma has been reported, but is much less studied. [64][65][66] In particular, subcutaneous treatment with heat-killed Mycobacterium vaccae was reported to induce CD4 1 CD45RB low T cells, which inhibited asthma through IL-10 and TGF-b production.…”
Section: Immune Deviationmentioning
confidence: 99%
“…34,36,38,57,63,64,66,104 We recently showed that the adoptive transfer of DCs from Schistosoma japonicum-infected mice dramatically decreased airway allergic inflammation and was associated with a significant decrease in IL-4/ IL-5 production and an increase in IL-10 production. 63 The DCs' modulating effect on allergy was related to enhanced CD4…”
Section: Critical Role Of Dcs In Infection-mediated Inhibition Of Allmentioning
confidence: 99%
See 1 more Smart Citation
“…Corroboraría la tendencia ya marcada en otros estudios previos, en los que el tiempo medio de evolución desde el momento de la inmigración oscilaba alrededor de los 5 años 16 . Una de las hipótesis para justificar esta rápida sensibilización se basaría en un cierto carácter protector por parte de las infecciones por helmintos, que estos sujetos sufrirían en sus países de origen, para modular la intensidad de la reacción alér-gica respiratoria 17,18 . Al desaparecer este efecto al llegar a los países más desarrollados, acabarían por sensibilizarse frente a los alérgenos a los que se ven expuestos.…”
Section: Discussionunclassified